The Impact of Peer Support (Buddy System) Intervention on the Academic Achievement and Social Development of Elementary School Students in Inclusive Classrooms in a Government School in Fujairah - ALZAABI, ONOUD (2024)
This dissertation examined the efficacy of a peer support strategy, specifically, a buddy system in inclusive classrooms at a government school in Fujairah. The study focused on how this intervention influenced the academic performance and social development of elementary school students. The investigation employed a mixed-methods research approach by integrating the quantitative evaluations of an academic performance standardised test and survey with the qualitative investigation of social development using interviews with students. This study used a semi-experimental approach which allowed insight into a real-world example of the use of peer support intervention in an inclusive classroom. The findings showed a notable beneficial effect of the buddy system on academic performance and social development. Statistical analysis found significant enhancements in academic performance measures, while the qualitative data revealed the development of strong peer relationships, better communication skills, and improved teamwork abilities in students participating in the buddy system. Heightened inclusivity and cooperation in the classroom setting were found from the data collected. This study emphasised the efficacy of peer support interventions, such as the buddy system, in promoting holistic growth among diverse student populations in inclusive educational settings. The dissertation highlighted the need to utilise cooperative and inclusive methods to enhance academic success and social development for all students in the government schools of Fujairah. Keywords: peer support, social development, academic achievement